2016
DOI: 10.1063/1.4963716
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Ni film with In0.53Ga0.47As: Phase formation and texture

Abstract: The solid-state reaction between Ni and In 0.53 Ga 0.47 As on an InP substrate was studied by X-ray diffraction (XRD) and scanning transmission electron microscopy-energy-dispersive X-ray spectroscopy techniques. Due to the monocrystalline structural aspect of the so-formed intermetallic, it was necessary to measure by XRD a full 3D reciprocal space mapping in order to have a complete overlook over the crystalline structure and texture of the intermetallic. The formation of the intermetallic was studied upon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Note that these two in-plane directions have been reported for a very different system, i.e. Ni/In 0.53 Ga 0.47 As (Group B domains) (Zhiou et al, 2016). The poles at = 55 might be related to the projection of the (111) planes of the TiN capping layer on the (001) plane.…”
Section: Nature Of the Ni-rich Phasementioning
confidence: 86%
“…Note that these two in-plane directions have been reported for a very different system, i.e. Ni/In 0.53 Ga 0.47 As (Group B domains) (Zhiou et al, 2016). The poles at = 55 might be related to the projection of the (111) planes of the TiN capping layer on the (001) plane.…”
Section: Nature Of the Ni-rich Phasementioning
confidence: 86%
“…However, in ref. , the onset was 300 °C which indicated a temperature offset and placed the in situ experiments on the higher end of the temperatures where Ni 2 In 0.53 Ga 0.47 As phase was observed. (3) The nickelide lattice constants were measured in a region far from the reaction interface (i.e., strain‐free), and the lattice constants were in agreement with those of Ni 2 In 0.53 Ga 0.47 As that were obtained in a prior study on planar structures .…”
Section: Methodsmentioning
confidence: 96%
“…Nickelide Phase Identification : Recent studies on planar nickelide reactions had identified a sequential formation of Ni 3 In 0.53 Ga 0.47 As, Ni 2 In 0.53 Ga 0.47 As, and NiAs with temperatures . Here, the nickelide phase was concluded as Ni 2 In 0.53 Ga 0.47 As due to the following reasons: (1) the study was carried out at temperatures lower than the decomposition temperature of the nickelide phase, and therefore out‐diffusion of In and Ga (which lead to the formation of NiAs phase) was not favoured.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations